The First-Principle Study on Wide-Gap Semiconductor Material $CuYO_2$ (Journal of Atomic and Molecular Sciences, 2021)
Using the first-principle method within the generalized gradient approximation, this paper studies the bands structure, structural parameters, and state densities of wide-gap semiconductor material $CuYO_2.$ The calculated results show that, the valence band of $CuYO_2$ mainly compose of $3d$ of $Cu,$ and $2p$ of $O;$ while the conduction band mainly compose of $3d$ of $Y.$ Through the $+U$ correction, with the increasing of the value of $U,$ the conduction band and valence band of $CuYO_2$ become split, the peak of $3d$ of $Y$ move towards high energy area, which induce to the enlarge of conduction band area and band gap; in addition, the minimum of conduction band is transfer $L$ point into $Γ$ point when the value of $U$ is 2eV, which show $+U$ method mainly correct the conduction band of $CuYO_2$ so that improve the calculated value of band gap.
Keywords: $CuYO_2$; band structure; first-principle method.